Party frequency, party-safety strategies, and sexual victimization among first-year female college students. Issue 6 (24th August 2022) - Jouriles, Ernest N.; Krauss, Alison; Sargent, Kelli S.; Nguyen, Jamie; Cascardi, Michele; Grych, John H.; McDonald, Renee
Abstract: Objective: This study examined whether the use of party-safety strategies weakens the association between frequency of party attendance and sexual victimization among first-year female college students. Participants: First-year female college students ( n = 450) from three universities in the United States participated in this study. Methods: Participants completed questionnaires on frequency of party attendance, use of party-safety strategies, and sexual victimization. Results: Frequency of party attendance was positively associated with sexual victimization. This association was moderated by use of party-safety strategies: frequency of party attendance was unrelated to sexual victimization when students reported greater use of party-safety strategies. However, frequency of party attendance was positively related to sexual victimization when students reported lower use of party-safety strategies. Conclusions: Teaching and reinforcing party-safety strategies may be helpful additions to efforts to prevent sexual victimization on college campuses.